A Case Report of Non-Bacterial Cystitis Caused by Immune Checkpoint Inhibitors - Zhu, Sihui; Bian, Lijuan; Lv, Jia; Liu, Baorui; Shen, Jie (Frontiers in Immunology, 2021)
We report a case of non-bacterial cystitis after treatment with programmed death-1 (PD-1) and programmed cell death-ligand 1 (PD-L1) antibodies, which was considered an immune-related adverse event (irAE). A 48-year-old male patient with intrahepatic cholangiocarcinoma (ICC) was treated with nivolumab after postoperative multi-line treatment. This patient recurred worsening of psoriasis and repeated urinary tract discomfort. The drug was discontinued and surgery was performed due to the recurrence of the tumor suggested by imaging. After receiving three cycles of chemotherapy treatment combined with atezolizumab, urinary tract discomfort reappeared. No bacteria were found in multiple urine cultures, and non-bacterial bladder inflammation was considered after cystoscopy biopsy. This is a report of non-bacterial inflammation of the urinary tract caused by immunotherapy.